Neuroanatomical correlates of individual differences in social anxiety in a non-clinical population. (3rd July 2016) - Tian, Xue; Hou, Xin; Wang, Kangcheng; Wei, Dongtao; Qiu, Jiang
Abstract : Socially anxious individuals are characterized as those with distorted negative self-beliefs (NSBs), which are thought to enhance reactions of social distress (emotional reactivity) and social avoidance (social functioning). However, it remains unclear whether individual differences in social distress and social avoidance are represented by differences in brain morphometry. To probe into these neural correlates, we analyzed magnetic resonance images of a sample of 130 healthy subjects and used the Connectome Computation System (CCS) to evaluate these factors. The results showed that social distress was correlated with the cortical volume of the right orbitofrontal cortex (OFC) and the subcortical volume of the left amygdala, while social avoidance was correlated with the cortical volume of the right dorsolateral prefrontal cortex (DLPFC). Additionally, loneliness might mediate the relationship between the amygdala volume and the social distress score. Our results demonstrated that social distress and social avoidance were represented by segregated cortical regions in the healthy individuals. These findings might provide a valuable basis for understanding the stable brain structures underlying individual differences in social anxiety.